Foundational pasts : the Holocaust as historical understanding - Confino, Alon 1959- (Cambridge University Press, 2012)
"This book proposes to understand the Holocaust by looking at Nazi and German culture and sensibilities that made the persecution and extermination imaginable, possible, and conceivable. It critically reviews the keycurrents in Holocaust historiography in the last generation, arguing for a new approach that places at the center not simply what happened during the Nazi years--the anti-Semetic ideological campaign, the machinery of killing, the brutal massacres during the way--but especially what the Nazi and other Germans thought was happening; a necessary, deathly war against the key enemy, the Jews"--